2015
DOI: 10.1016/j.biomaterials.2015.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonally oriented scaffolds with aligned fibers for engineering intestinal smooth muscle

Abstract: Controlling cellular alignment is critical in engineering intestines with desired structure and function. Although previous studies have examined the directional alignment of cells on the surface (x-y plane) of parallel fibers, quantitative analysis of the cellular alignment inside implanted scaffolds with oriented fibers has not been reported. This study examined the cellular alignment in the x-z and y-z planes of scaffolds made with two layers of orthogonally oriented fibers. The cellular orientation inside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 36 publications
1
36
0
Order By: Relevance
“…In the field of tissue engineering, cell behaviors are affected by multiple types of inductive biomaterial signals, such as the structures, released chemical molecules, and mechanics of scaffolds (Kobayashi, Lei, Wang, Wu, & Dunn, 2015;Liu et al, 2013;Wang, Hu, Kawazoe, Yang, & Chen, 2016;Zhong et al, 2006). Studies have been proposed on the effects of chemistry and topography on cell behaviors, but the synergistic effect of these two signals in cell behavioral regulation and its possible mechanisms have not been extensively studied.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the field of tissue engineering, cell behaviors are affected by multiple types of inductive biomaterial signals, such as the structures, released chemical molecules, and mechanics of scaffolds (Kobayashi, Lei, Wang, Wu, & Dunn, 2015;Liu et al, 2013;Wang, Hu, Kawazoe, Yang, & Chen, 2016;Zhong et al, 2006). Studies have been proposed on the effects of chemistry and topography on cell behaviors, but the synergistic effect of these two signals in cell behavioral regulation and its possible mechanisms have not been extensively studied.…”
mentioning
confidence: 99%
“…To improve the mechanical strength and supply a topological signal for attached cells, aligned electrospun fibers were fabricated (Yang, Deng, Chen, Ye, & Mo, 2014). These fibers are usually collected on rotating mandrels, leading to controllable mechanical and structural anisotropy, and the anisotropic fiber scaffolds are ideal for tendon, ligament, muscle, and nerve tissue engineering (An, Chua, Leong, Chen, & Chen, 2012;Kobayashi et al, 2015). Selected studies have shown that human gingiva produced an anisotropic response, and the aligned fibers were useful in guiding cell growth with the desired anisotropy (Kobayashi et al, 2015;Kydd & Mandley, 1967).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen has been used in many tissue engineering applications, often in conjunction with other treatments 25,26 , and specifically for intestine 27,28 and intestinal smooth muscle 2931 . Tissue-engineered smooth muscle constructs have used collagen extensively, both as a substrate 15 and as a coating to enhance cell attachment to polymers 29 .…”
Section: Introductionmentioning
confidence: 99%
“…However, pure polymeric nanofibers are suitable mainly for soft tissue engineering, such as reconstruction and regeneration of blood vessels [13,22,23,31,32], myocardium [33,34], heart valves [35,36], skeletal muscle [37,38], skin [15, [39][40][41], tendon and ligament [42,43], intestine [44,45], tissues of the respiratory system, such as trachea and bronchi [46,47], components of urinary tract, such as bladder [48] and urethra [49], visceral organs, such as liver [50,51] or pancreas (pancreatic islets [52,53]), central nervous system, such as brain [6,54,55], spinal cord [56,57], optic system, such as optical nerve [58] and retina [59], and peripheral nervous system [17,60]. Nanofibrous scaffolds can be associated with another advanced technique in recent tissue engineering-controlled delivery of various types of stem cells, such as bone marrow mesenchymal stem cells [51,[61][62][63], adipose tissue-derived stem cells [64,65], neural tissue-derived stem cells [57], and induced pluripotent stem cells …”
Section: Introductionmentioning
confidence: 99%